ANALYSIS OF LEVELS IN SCOUTING IN REALIZING A SENSE OF NATIONALISM - Khafifah Rahmawani Siregar; Setiyani Br Saragih; Padilah Hoiriah Harahap (CV. Asry Persada Quality, 2024)
The type of research used in this research is qualitative research. The data collection techniques used in this research are as follows: (1) Observation (Observation, documentation and traiangulation. The results of the research. Nationalism at the scout level is a manifestation of national awareness or national spirit. How does nationalism develop? application of a national way of thinking. National thinking can also be antithetical to regional or group ways of thinking. New behavior occurs when there is something that is needed to cause a reaction, namely stimulation, then the stimulus will cause a reaction or behavior. A form of human behavior that is invisible or hidden ( convert behavior) and visible behavior (overt behavior). nationalism at the scout level or nationalism within each paramuka member.